CONTESTATION OR ADAPTATION: MODE OF MAINTAINING CACAH JIWA TRADITION IN THE INDIGENOUS COMMUNITY OF KASEPUHAN CISUNGSANG LEBAK, BANTEN - Noorbani, Muhammad Agus; Hamida, Siti Nurul; Nur, Mahmudah; Bahri, Saeful (Al-Qalam, 2023)
This paper presents the results of research on the tradition of Cacah Jiwa or prah-prahan in Kasepuhan Cisungsang Lebak, Banten. Banten is inhabited by the diversity of population backgrounds, cultures, languages, and religions that makes Banten as an attractive area and holds the potential for conflict. Conflicts that often occur are always related to the contestation between adherents of religion (Islam) and adherents of various local beliefs, which are still held by some Banten residents, especially those who live in the kasepuhan community. This paper, using interview and observation methods in data collection, aims to analyze how the tradition of prah-prahan is still maintained. This paper shows that Cacah Jiwa ritual is maintained by mixing and matching with Islamic teachings as a belief that recently come. This ritual signifies that indigenous peoples prioritize modes of adaptation in maintaining their traditions. This dismisses the view that there is a contestation between traditional actors and religious teachings and their adherents. For the indigenous people of Kasepuhan Cisungsang, tradition must not violate religious law; traditional practices and religious practices must be within the corridor of state law. Cacah Jiwa contains various prayers to The Almighty, which are read by the perpetrators, conveying wasilah to the ancestors, both the propagator of the religion they profess and the traditional ancestors. These prayers describe their beliefs as followers of Islamic religion. This tradition also teaches the indigenous community to be sensitive to the condition of their relatives, continue to build friendships, and uphold brotherhood.